PENINGKATAN HASIL BELAJAR SENAM LANTAI GERAKAN ROLL BELAKANG DENGAN MENGGUNAKAN ALAT BANTU SPON DAN KARET BAN DALAM SEPEDA MOTOR PADA SISWA SD NEGERI SRONDOL 02 KOTA SEMARANG TAHUN AJARAN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the improvement of learning outcomes gymnastics floor rear roll motion using a sponge and rubber tools motorcycle tires in the VB graders Srondol Elementary School 02 Semarang Academic Year 2013/2014. The method of this study is action research with the research subject is the VB class 02 SD Negeri Semarang Srondol consisting of 30 students. The first cycle administered questionnaire, assessment by using a sheet instruments of aspects of affective, cognitive, and psychomotor . In the second cycle is given in the form of instructional media in a motorcycle tire rubber and sponge. conclusions using the tools sponge and rubber tires in the motorcycle can improve student learning outcomes in V B class in elementary school Srondol 02 of Semarang students more easily understand and rear roll movement the results of student success in the second cycle which gained mastery learning outcomes of students 93% and the average grade in the first cycle 81. Compared who only earn passing grade of 37% and an average of 68 classes